INTERACT: um modelo baseado em contextos para motivação de interações em redes sociais - Santos, Marcelo da Silva dos (Universidade do Vale do Rio dos Sinos, 2017)
The popularization of the use of virtual social networks in increasingly young layers of society has become part of daily life. In this sense, new implementations of Social Network, such as the Spontaneous Social Network (SSN), emerge. Unlike traditional social networks, where social interactions are often an extension of existing relationships in the real world, SSN starts from the premise that there is no need for prior relationships between participants. Considering that even in groups formed by participants that are known for a long time it is not possible to assure any kind of virtual active interaction, in spontaneous social networks this fact could become reason to discourage its use. The objective of this work is the construction of a model capable of extracting information from groups using social networks, allowing determining the profile of the group from the information extracted from the contextual histories of its member users, and with this to recommend resources capable of influencing the Interaction between members. In this scenario, INTERACT is a model that has as main scientific contribution to use the contextual histories of the users of a Spontaneous Social Network or any other social network to encourage interactions among its participants. The use of historical as a resource to enhance the interactions was identified as a difference in relation to the works related to the areas of which, for the most part, only use the current context as a way to generate punctual actions and without relationship with other participants. For the evaluation of the model, a group of volunteers was invited to participate in an experiment in which INTERACT interacted with the group through a person created. The analysis was performed quantitatively and qualitatively, through the collection of numbers generated in interactions among the participants, activity records and questionnaires. The results indicate an increase in the volume of interactions between the participants in the moments of performance of the prototype. The participants also reported a positive influence of the actions of the person managed by the prototype, recognized by the group as a influential "member".
Keywords: Ciência de contexto; Redes sociais; Computação ubíqua; Sistemas de recomendação; Interação; Context awareness; Social network; Ubiquitous computing; Motivation; Interaction; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação